DIALOG SEMIOTIKA IDENTITAS PRODUK: NEGOSIASI SIMBOL TRADISIONAL DALAM DESAIN PRODUK MODERN: DIALOG SEMIOTIKA IDENTITAS PRODUK: NEGOSIASI SIMBOL TRADISIONAL DALAM DESAIN PRODUK MODERN - Rahmawan Dwi Prasetya; Sekar Adita; Mochamad Junaidi Hidayat (Ide dan Dialog Desain Indonesia (Idealog), 2026)
Abstract: This study examines symbolic negotiation in three-dimensional product design that integrates traditional elements into modern design contexts. Previous studies on cultural artefacts and product design have largely emphasised qualitative narratives, while empirical testing of user perception toward three-dimensional visual units remains limited. Therefore, this research proposes the Symbolic Negotiation Matrix as its main novelty, distinguishing fixed and fluid design elements through morphological decomposition and perceptual validation. This study aims to formulate a systematic framework for the decomposition of three-dimensional geometric units and to validate its impact on user identity recognition. The study applies a sequential exploratory strategy, beginning with a qualitative morphological audit of the Tegal clay teapot as a case object, followed by a quantitative survey using a semantic differential scale involving 85 respondents. The findings show a significant difference in identity recognition across design variables, χ² (3, N = 340) = 42.47; p < 0.001; Cramer’s V = 0.35. Volume proportion achieved the highest recognition rate, reaching 88 percent or 75 out of 85 respondents, followed by construction logic at 74 percent or 63 out of 85 respondents. The study concludes that successful transformation of cultural products does not rely merely on surface ornamentation but on the designer’s ability to preserve morphological structures that function as identity anchors. Keywords: semiotics; product design; traditional symbols; 3D visual units; design negotiation